Optical analysis of nanostructured rose bengal thin films using Kramers–Kronig approach: New trend in laser power attenuation. (15th April 2019) - Aslam Manthrammel, M.; Aboraia, A.M.; Shkir, Mohd; Yahia, I.S.; Assiri, Mohammed A.; Zahran, H.Y.; Ganesh, V.; AlFaify, S.; Soldatov, Alexander V.
Highlights: Rose Bengal thin films were deposited on glass substrates with different thicknesses. Refractive and extinction indices values are calculated by Kramers-Kronig calculations. Third-order nonlinear optical susceptibility and refractive index values were estimated. Optical limiting is found to be enhanced by increasing the film thickness. Rose Bengal is a promising candidate for wide-scale optoelectronic applications and laser power attenuation. Abstract: Highly stable Rose Bengal (RsB) organic semiconductor thin films were deposited on glass substrates with different thicknesses ranging from 95 to 325 nm. Optical transmission, reflection, and absorption studies were employed to analyze various optical constants. Refractive index and extinction coefficient values were attained using Kramers-Kronig calculations from the reflectance data. Dielectric constant, loss and dissipation factor were studied. Third-order nonlinear optical susceptibility and refractive index values were estimated using linear refractive index and absorption coefficient data for RsB films and studied their properties in nonlinear media. Optical limiting characteristics are found to be enhanced by increasing the thicknesses of films. The studied films can be used to limit the laser power of wavelengths 632 nm and 532 nm as an optical limiting material. The present work suggests that film of RsB is a promising candidate for wide-scale optoelectronic applications including IR pass filter, laser power attenuation, and selective CUT-OFF laser filters in the wavelength range 490–595 nm.